Establishment of CD-ROM Based Infromation System - Plans and Prospects - Balarama (Journal of Information and Knowledge, 1988)
Presents on overview of the official disc technology. Basics of CD-ROM technology and production of the same are discussed. CD-ROM Databases, softwares for CD-ROM, methods of gathering and handling and the value of these systems are delineated.